PENGGUNAAN DISINFEKTAN KIMIA DAN DISINFEKTAN TRADISIONAL TERHADAP PENURUNAN JUMLAH MIKROBA PADA SIKAT GIGI - Putri, Andini S.K.; Hidayati, Sri; Ulfah, Siti Fitria (Politeknik Kementerian Kesehatan Banjarmasin, 2022)
Abstract: An effective preventive measure for dental and oral diseases is brushing teeth, but toothbrushes can be a means of transmitting pathogenic microorganisms that cause systemic diseases and oral diseases. It is recommended to replace a toothbrush every 3 months so that bacteria does not accumulate, but the average Indonesian people replace it at least once every 10 months. Objective: To determine the use of chemical disinfectants and traditional disinfectants to reduce the number of microbes on toothbrushes. Methods: Literature review, articles obtained through the Google Scholar database (2016-2021) using PICOS as a determinant of inclusion criteria and exclusion criteria. Results: The effective chemical disinfectants were 2% NaOCl, listerine, chlorhexidine gluconate, and povidone iodine, while the effective traditional disinfectants were vinegar with 5-8% glacial acetic acid, 1% vinegar, 38% white vinegar mixed with salt solution. 3.5%, 50% white vinegar solution, 38% white vinegar solution, garlic, lime juice, rosella flower decoction, neem, guava leaves, green tea leaves, papaya leaves, baking soda, salt, and black tea leaves. Conclusion: Chemical disinfectants that have been shown to reduce the number of bacteria on toothbrushes are NaOCl 2% and traditional disinfectants that have been shown to reduce the total number of microbes on toothbrushes are vinegar with 5-8% glacial acetic acid, and 1% vinegar and 38 white vinegar solution. % mixed with a 3.5% salt solution has been shown to reduce the total number of bacteria on the toothbrush. Keywords: Toothbrush disinfection; Chemical Disinfectant; Traditional Disinfectants